Syari’at Islam dan Qanun Jinayat di Aceh - Hasanuddin Yusuf Adan (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Abstract: The history of the implementation of Islamic law in Aceh has taken a very long time since the colonial era to the reform era in Indonesia. All of this happened more because of the government and government that started from the Dutch East Indies government to the Old Order, New Order and Reformation. However, in the end, the Law for the implementation of Islamic Shari'ah in Aceh came down from Jakarta, starting with the Law. No. 44 of 1999 concerning the Privileges of Aceh up to Law No. 11 of 2006 concerning the Government of Aceh. As a mandate from the law, a number of laws were born to complete the operational implementation of Islamic law in Aceh. This study uses historical research methods because the study of material is related to the history of the implementation of Islamic law in Aceh. The findings of this study indicate that the struggle for the implementation of Islamic law in Aceh requires a long struggle so that it meets with success.Abstrak: Sejarah pelaksanaan syari’at Islam di Aceh mengalami uluran waktu yang sangat panjang semenjak zaman kolonial sampai kepada zaman reformasi di Indonesia. Semua itu terjadi lebih disebabkan oleh perjalanan pemerintahan dan birokrasi yang bermula dari pemerintahan Hindia Belanda sampai kepada rezim Orde Lama, Orde Baru dan Orde Reformasi. Walaubagaimanapun, akhirnya Undang-undang pemberlakuan syari’at Islam di Aceh turun dari Jakarta, mulai dari Undang-Undang Nomor 44 Tahun 1999 Tentang Keistimewaan Aceh sampai kepada Undang-Undang Nomor 11 Tahun 2006 Tentang Pemerintahan Aceh. Sebagai amanah dari undang-undang tersebut maka lahirlah sejumlah qanun untuk melengkapi perangkat operasional pelaksanaan syari’at Islam di Aceh. Penelitian ini menggunakan metode penelitian historis karena kajian materinya terkait dengan pemaparan sejarah pelaksanaan syari’at Islam di Aceh. Hasil temuan dari penelitian ini menunjukkan bahwa perjuangan pelaksanaan syari’at Islam di aceh memerlukan perjuangan panjang sehingga ketemu dengan kesuksesan.